Analysis of Influencer Strategies in Shaping Young People’s Wellness Lifestyles in Bali - Ayu Made Bianca Juarez; Sahri Aflah Ramadiansyah; Putri Ekaresty Haes (Doctoral Program of Social Science Pasundan University, 2026)
The proliferation of digital health content has fundamentally transformed how Generation Z adopts wellness habits, yet it also introduces risks such as health misinformation and unrealistic body ideals. This study is significant as it explores social media's role within Bali’s global wellness hub. Despite extensive marketing literature, a research gap exists regarding how influencers move beyond transactional promotion toward the long-term internalization of preventive health behaviors. This research aims to analyze the communication strategies and impression management techniques used by Bali based wellness influencers to cultivate sustainable lifestyles. Utilizing a qualitative descriptive method, data were gathered through the triangulation of digital observations on TikTok and Instagram, semi-structured interviews, and documentation. Findings reveal that influencers leverage Bali’s